Interactions of Bacteriophages and Bacteria at the Airway Mucosa: New Insights Into the Pathophysiology of Asthma - Tzani-Tzanopoulou, Panagiota; Skliros, Dimitrios; Megremis, Spyridon; Xepapadaki, Paraskevi; Andreakos, Evangelos; Chanishvili, Nina; Flemetakis, Emmanouil; Kaltsas, Grigoris; Taka, Styliani; Lebessi, Evangelia; Doudoulakakis, Anastassios; Papadopoulos, Nikolaos G. (Frontiers in Allergy, 2021)
The airway epithelium is the primary site where inhaled and resident microbiota interacts between themselves and the host, potentially playing an important role on allergic asthma development and pathophysiology. With the advent of culture independent molecular techniques and high throughput technologies, the complex composition and diversity of bacterial communities of the airways has been well-documented and the notion of the lungs' sterility definitively rejected. Recent studies indicate that the microbial composition of the asthmatic airways across the spectrum of disease severity, differ significantly compared with healthy individuals. In parallel, a growing body of evidence suggests that bacterial viruses (bacteriophages or simply phages), regulating bacterial populations, are present in almost every niche of the human body and can also interact directly with the eukaryotic cells. The triptych of airway epithelial cells, bacterial symbionts and resident phages should be considered as a functional and interdependent unit with direct implications on the respiratory and overall homeostasis. While the role of epithelial cells in asthma pathophysiology is well-established, the tripartite interactions between epithelial cells, bacteria and phages should be scrutinized, both to better understand asthma as a system disorder and to explore potential interventions.